Tantangan dan Strategi Pengawasan Partisipatif oleh Bawaslu Sleman: Studi Empiris Pilkada Sleman 2024 - Baskoro, Aji; Mochamad Adli Wafi (UIN Sunan Kalijaga Yogyakarta, 2025)
Participatory election monitoring serves as a crucial instrument to ensure transparency, accountability, and integrity within the democratic process. Although it has been granted a legal foundation through Bawaslu Regulation No. 2 of 2023 on Participatory Monitoring, its implementation at the local level still faces numerous challenges. This study aims to identify both the obstacles and strategies for optimizing participatory election monitoring. Employing an empirical juridical method, it examines the existing legal provisions and their practical application through direct observation and focus group discussions. The study focuses on participatory monitoring practices conducted by Bawaslu Sleman in collaboration with the Center for Democracy, Constitution, and Human Rights Studies (PANDEKHA) across fifteen community forums ahead of the 2024 Simultaneous Regional Elections. The main gap identified lies in the discrepancy between the ideal legal norms and the actual practices of citizen participation, which have yet to become fully institutionalized. Implementation challenges appear in two dimensions: structural and cultural. Structural challenges include difficulties in disseminating electoral materials across diverse social groups, obstacles in managing public reports that often fail to meet legal evidentiary standards, and the absence of safe spaces for whistleblowers. Meanwhile, cultural challenges are related to the low collective awareness of clean election values, permissive attitudes toward vote buying, and limited digital literacy among older voters. The findings reveal that participatory monitoring should be conducted throughout all stages of the election process, not merely during the campaign period. The structural approach emphasizes strengthening regulations, reporting mechanisms, and the capacity of election monitoring institutions, whereas the cultural approach highlights improving political literacy and fostering a more inclusive democratic culture. Pengawasan partisipatif dalam pemilihan umum merupakan instrumen penting untuk memastikan transparansi, akuntabilitas, dan integritas proses demokrasi. Kendati telah memiliki dasar hukum melalui Peraturan Bawaslu No. 2 Tahun 2023 tentang Pengawasan Partisipatif, pelaksanaannya di tingkat lokal masih menghadapi berbagai kendala. Penelitian ini bertujuan untuk mengidentifikasi tantangan dan strategi optimalisasi pengawasan partisipatif. Menggunakan metode yuridis empiris, penelitian ini mengkaji ketentuan hukum yang berlaku serta implementasinya melalui observasi langsung dan forum group discussion. Studi dilakukan terhadap pelaksanaan pengawasan partisipatif oleh Bawaslu Sleman bersama Pusat Kajian Demokrasi, Konstitusi, dan HAM (PANDEKHA) di lima belas forum warga menjelang Pilkada Serentak 2024. Celah utama yang ditemukan terletak pada kesenjangan antara norma hukum yang bersifat ideal dengan praktik partisipasi masyarakat yang belum sepenuhnya terinstitusionalisasi. Tantangan implementasi muncul dalam dua dimensi: struktural dan kultural. Tantangan struktural meliputi kesulitan penyampaian materi kepemiluan lintas kelompok sosial, kendala dalam pengelolaan laporan masyarakat yang sering belum memenuhi standar pembuktian hukum, serta belum tersedianya ruang aman bagi pelapor. Sementara itu, tantangan kultural berkaitan dengan rendahnya kesadaran kolektif terhadap nilai pemilu bersih, pandangan permisif terhadap politik uang, dan keterbatasan literasi digital di kalangan pemilih generasi lebih tua. Hasil penelitian menunjukkan bahwa pengawasan partisipatif seharusnya dapat dilakukan di seluruh tahapan pemilu, tidak terbatas pada masa kampanye. Pendekatan struktural menekankan penguatan regulasi, mekanisme pelaporan, dan kapasitas lembaga pemantau pemilu, sementara pendekatan kultural menitikberatkan pada peningkatan literasi politik masyarakat dan pembangunan budaya demokrasi yang lebih inklusif.